UPAYA MENINGKATKAN KINERJA GURU MELALUI SUPERVISI EDUKATIF KOLABORATIF DI SDN 01 MADIUN LOR KOTA MADIUN - Billah Zaharuddin, Arif; Sudarmiani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe teacher performance, describe the implementation of collaborative educational supervision as an effort to improve teacher performance, and analyze the improvement of teacher performance through collaborative educational supervision at SDN 01 Madiun Lor, Madiun City. The research method used is school action research with the subjects of the principal and 8 teachers at SDN 01 Madiun Lor, Madiun City. Data were collected using observation, interview, and documentation techniques and analyzed qualitatively using the Miles and Huberman model. This study was conducted in two cycles, with four stages: planning, implementation, observation, and reflection. The results of the study showed that teacher performance before the implementation of collaborative educational supervision was still low, then after the implementation of collaborative educational supervision experienced an increase and in the second cycle achieved completeness with teacher performance reaching the very good category. The implementation of collaborative educational supervision was carried out by the Principal of SDN 01 Madiun Lor as a supervisor and researchers as collaborators with supervision subjects consisting of 8 teachers. In the pre-cycle, the average teacher performance was only 62.6%, or in the adequate and unsuccessful category. After collaborative educational supervision, the average success rate of teacher performance improvement in cycle I was only 70.6%, while in cycle II it reached 94.3%. This suggests that collaborative educational supervision has successfully improved teacher performance at SDN 01 Madiun Lor, Madiun City. Based on the findings of this action research, collaborative educational supervision for all teachers needs to be conducted periodically and established at the beginning of the school year. The principal must coordinate with teachers and motivate them to learn from each other.